Penerapan Problem Based Learning Dengan LKPD Liveworksheet Untuk Meningkatkan Hasil Belajar Fisika Siswa Kelas X - Diana Anjar Wati; Sugiarti (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
The low physics learning outcomes of students need to be overcome by applying the right learning model and learning media. Through the problem-based learning model with LKPD Liveworksheet, students are guided in the learning process activities that involve students actively. Learners are guided in solving problems through LKPD with worksheets in accordance with current technological developments so that students are more active. This research is a class action research conducted in two cycles, involving class X.5 SMA Negeri 8 Palembang as many as 36 students as research subjects, which aims to improve student learning outcomes through the application of problem-based learning. The data collection method used was an objective test which was analyzed using quantitative descriptive analysis techniques. The results of this study showed that there was an increase from the pretest by 6% with an average of 61 increased in cycle I by 17% with an average of 68, and increased in cycle II by 64% with an average of 81. So it can be said that the application of the problem-based learning model with LKPD liveworksheet can improve student learning outcomes.